A interface entre distúrbio obsessivo-compulsivo e esquizofrenia: Desafios da prática clínica - Torres, Albina Rodrigues [UNESP]; Smaira, Sumaia Inaty [UNESP]; Ferreira, Domingos T. J. [UNESP] (My University, 1997)
The article discusses the relationship between obsessive-compulsive disorder (OCD) and schizophrenia, based on the report of eight clinical cases. It describes and discusses cases of OCD with poor insight, obsessions that seem paranoid delusions or auditive hallucinations, OCD with transient psychotic reactions, OCD with schizotypal personality disorder and schizophrenia with obsessive-compulsive symptoms.
The interface between obsessive-compulsive disorder and schizophrenia: Challenges of clinical practice
Keywords: Comorbidity; Differential diagnoses; Obsessive-compulsive disorder; Schizophrenia